2012
DOI: 10.1155/2012/285328
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Blocks Provided Sustained Pain Relief in a Patient with Refractory Painful Diabetic Neuropathy

Abstract: The sympathetic nervous system has been implicated in pain associated with painful diabetic neuropathy. However, therapeutic intervention targeted at the sympathetic nervous system has not been established. We thus tested the hypothesis that sympathetic nerve blocks significantly reduce pain in a patient with painful diabetic neuropathy who has failed multiple pharmacological treatments. The diagnosis of small fiber sensory neuropathy was based on clinical presentations and confirmed by skin biopsies. A series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…It has consistently been shown that the administration of dexamethasone can prolong analgesia after peripheral nerve block [ 21 ]. One case report showed that the use of a mixture of lidocaine and triamcinolone in a lumbar sympathetic block was able to significantly reduce the pain scores of the patient with painful diabetic neuropathy [ 11 ]. It has also been suggested that damaged nerve fibers often have dysregulated expression of sodium channels that are particularly sensitive to local anesthetics, such as lidocaine [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has consistently been shown that the administration of dexamethasone can prolong analgesia after peripheral nerve block [ 21 ]. One case report showed that the use of a mixture of lidocaine and triamcinolone in a lumbar sympathetic block was able to significantly reduce the pain scores of the patient with painful diabetic neuropathy [ 11 ]. It has also been suggested that damaged nerve fibers often have dysregulated expression of sodium channels that are particularly sensitive to local anesthetics, such as lidocaine [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of the peripheral blood flow may be involved in the mechanism of the analgesic effect of spinal cord stimulation. In China, spinal cord stimulation for treating neuropathic pain is not in wide use due to the high cost of the treatment; as alternative, another non-pharmacological approach, lumbar sympathetic blockade, has received much interest [ 11 ]. Lumbar sympathetic blockade has the advantage of being a minimally invasive technique, with patients usually having a quick recovery time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both pain management and surgical analgesia is a challenge in patients with diabetes mellitus. 1,2 The present management options for diabetic polyneuropathy include stringent glycemic control and pain management by pharmacotherapy such as opioids, anticonvulsants, tricyclic antidepressants, selective serotonin, and noradrenaline reuptake inhibitors, anesthetic patches, etc. However, the management of pain in diabetic neuropathy still remains a challenge to clinicians as the current strategies are not satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…However, the management of pain in diabetic neuropathy still remains a challenge to clinicians as the current strategies are not satisfactory. 1,2 An effective tool for analgesia in both Type 1 and Type 2 diabetic patients for perioperative management and pain control is peripheral nerve blocks. In the case of surgery, peripheral nerve block provides better and prolonged anesthesia than general anesthesia and also avoids the insulin-resistance and cardiopulmonary effects of general anesthesia.…”
Section: Introductionmentioning
confidence: 99%